Parametric studies of failure mechanisms in thermal barrier coatings during thermal cycling using FEM - Srivathsa, Boddapati; Das, D.K. (Zielona Góra: Uniwersytet Zielonogórski)
Thermal barrier coatings (TBCs) are widely used on different hot components of gas turbine engines such as blades and vanes. Although, several mechanisms for the failure of the TBCs have been suggested, it is largely accepted that the durability of these coatings is primarily determined by the residual stresses that are developed during the thermal cycling.
Keywords: thermal barrier coatings; residual stresses; failure mechanisms; modeling; simulation